2008
DOI: 10.1111/j.1551-2916.2008.02409.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐Temperature Stability of Lanthanum Orthophosphate (Monazite) on Silicon Carbide at Low Oxygen Partial Pressures

Abstract: The stability of lanthanum orthophosphate (LaPO4) on SiC was investigated using a LaPO4‐coated SiC fiber at 1200°–1400°C at low oxygen partial pressures. A critical oxygen partial pressure exists below which LaPO4 is reduced in the presence of SiC and reacts to form La2O3 or La2Si2O7 and SiO2 as the solid reaction products. The critical oxygen partial pressure increases from ∼0.5 Pa at 1200°C to ∼50 Pa at 1400°C. Above the critical oxygen partial pressure, a thin SiO2 film, which acts as a reaction barrier, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 48 publications
2
41
0
Order By: Relevance
“…Comparisons of results from the two methods led to the conclusion that the Weibull modulus m obtained using nominal strengths is the same as that obtained using true strengths. That study has since served as the principal basis for justifying continued use of nominal fiber strengths …”
Section: Introductionmentioning
confidence: 99%
“…Comparisons of results from the two methods led to the conclusion that the Weibull modulus m obtained using nominal strengths is the same as that obtained using true strengths. That study has since served as the principal basis for justifying continued use of nominal fiber strengths …”
Section: Introductionmentioning
confidence: 99%
“…The YPO 4 ‐coated fibers were oxidized in laboratory air at 1000°C for up to 100 hours or 1200°C for 1 hour to form a silica layer on SiC. In prior work, good surface and grain boundary wetting of monazite (LaPO 4 ) by SiO 2 was observed during oxidation of monazite‐coated SiC fibers . It was therefore anticipated that during oxidation, silica might infiltrate porous YPO 4 coatings.…”
Section: Methodsmentioning
confidence: 99%
“…In our prior work, we showed that La 2 Si 2 O 7 formed when LaPO 4 ‐coated SiC fibers were heat treated in argon/low pO 2 mixtures . We also developed a process to apply continuous YPO 4 coatings on Nextel 720 fiber tows using a hetero‐precipitation method .…”
Section: Methodsmentioning
confidence: 99%
“…We also developed a process to apply continuous YPO 4 coatings on Nextel 720 fiber tows using a hetero‐precipitation method . Based on the formation of La 2 Si 2 O 7 , a thermodynamic analysis of reaction was conducted and experimental conditions for the formation of a single‐phase Y 2 Si 2 O 7 from YPO 4 on SiC fibers were determined . The details of the thermodynamic analysis and relevant experiments will be published elsewhere.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation